Carbon injection potential of the mesopelagic-migrant pump in the Southern Ocean during summer - Katherine Baker; Katherine Baker; Svenja Halfter; Svenja Halfter; Ben Scoulding; Kerrie M. Swadling; Kerrie M. Swadling; Shane A. Richards; Matthieu Bressac; Matthieu Bressac; Caroline A. Sutton; Philip W. Boyd; et al. (Frontiers in Marine Science)
The passive sinking flux of particles, termed the biological gravitational pump (BGP), is an important component of the ocean’s biological carbon pump. In addition, carbon-rich particles are actively injected to depth through the diel vertical migration (DVM) of micronekton and mesozooplankton from the surface to the oceans’ twilight zone (200 m – 1000 m depth). This is known as the mesopelagic-migrant pump (MMP). We investigated the magnitude of the MMP at one subantarctic and two polar sites in summer by assessing particulate and dissolved carbon export below 200 m depth based on DVM and the composition of the mesopelagic community. Carbon injection potential (CIP) for the dominant taxa at each site was estimated through four pathways, i.e., excretion, respiration, fecal pellets, and carcass production. Blooms of two migratory tunicate species, the pyrosome Pyrosoma atlanticum (subantarctic) and the salp Salpa thompsoni (polar) dominated the micronekton biomass and MMP export ranged from 5.0 to 9.4 mg C m-2 d-1 across the three Southern Ocean sites. Mesozooplankton abundance was dominated by copepods, which contributed an additional 0.7 to 32.2 mg C m-2 d-1 to the MMP. Results from this summertime study suggest an increase in the relative importance of the MMP compared to the BGP south of the Polar Front, however, future work should target the seasonality of the MMP, which necessitates linking environmental drivers to micronekton and mesozooplankton community composition, life history, and DVM.